2020
DOI: 10.1007/s41042-020-00042-8
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Clients’ Strengths: The Benefits of Using the Balanced Diagnostic Impressions (DICE-PM) Model

Abstract: People are generally prone to the negativity bias, and subsequently, psychological assessment has historically focused on pathology. Breaking with that tradition, research supports the effectiveness of infusing strengths in clinical practice to provide a more balanced approach. However, little research has examined the outcomes of providing education to students about intentionally using balanced assessment approaches. The purpose of this study was to examine the impact of teaching students about and the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…In a college student sample, strengths knowledge was related to well-being (Govindji & Linley, 2007), and in a longitudinal study, strengths knowledge was related to enhanced strengths use and greater academic satisfaction (Allan et al, 2019a). From a larger data set that corresponded with this study, previous analyses showed students exposed to strengths-based assessment instruction reported: greater perceived importance of strengths-based counseling and assessment services, wanting to know more about a greater number of client strengths in a low pathology vignette, and enhanced life satisfaction (Owens & Motl, 2020).…”
Section: Strengths-based Approachesmentioning
confidence: 72%
See 3 more Smart Citations
“…In a college student sample, strengths knowledge was related to well-being (Govindji & Linley, 2007), and in a longitudinal study, strengths knowledge was related to enhanced strengths use and greater academic satisfaction (Allan et al, 2019a). From a larger data set that corresponded with this study, previous analyses showed students exposed to strengths-based assessment instruction reported: greater perceived importance of strengths-based counseling and assessment services, wanting to know more about a greater number of client strengths in a low pathology vignette, and enhanced life satisfaction (Owens & Motl, 2020).…”
Section: Strengths-based Approachesmentioning
confidence: 72%
“…This suggests equivalence among the two groups and that the inclusion of strengths in abnormal psychology curriculum does not deter from learning about disorders. Given the many benefits of using strengths-based approaches for students, clinicians, and clients (e.g., Allan et al, 2019b; Owens & Motl, 2020; Rashid, 2015), it appears the incorporation of strength-based assessment in abnormal psychology courses holds promise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just as clinical diagnoses can change over time, so can each aspect of the DICE-PM Model, thus revisiting this model regularly throughout the course of clinical services is encouraged (Owens et al, 2015). Previous research has shown using the DICE-PM Model is effective in shifting individuals' focus toward a more balanced, strengths-based perspective (Owens & Motl, 2018); therefore, its use appears beneficial.…”
Section: The Balanced Diagnostic Impressions (Dice-pm) Modelmentioning
confidence: 99%